Cross-cultural analysis of cognitive attributions of smoking in Thai and South Korean adolescents - Page R. (2017)
Background: Understanding the cognitive attributions of smoking has the potential to advance youth smoking prevention efforts; however, research on this subject is limited in Asian countries. We attempted to determine the degree to which cognitive attributions of smoking differ among adolescents in 2 Asian countries, Thailand and South Korea. Methods: We surveyed 10th- to 12th-grade students in Chiang Mai, Thailand (N = 2516) and Seoul, South Korea (N = 1166). Logistic regression determined association of attributions and current smoking and differences in attributions between Thai and South Korean students. Results: Items with the highest agreement among South Koreans were "helps me to deal with stress" and "helps relax" and among Thai were "feel like I am making my own decisions" and "keeps from being bored." Significant predictors of current smoking were different between samples. Only 1 cognitive attribution predicted current smoking in both samples ("helps me to deal with stress"). Conclusion: The pattern of relevant cognitive attributions of smoking for the 2 samples was distinct, suggesting that cross-cultural differences merit consideration when designing prevention and cessation programs. Health education should strive to dispel the use of smoking as a coping strategy for dealing with stressful situations and distressful feelings and teach adolescents alternative healthy strategies for dealing with stress. © 2012, American School Health Association.